2004
DOI: 10.1002/nbm.891
|View full text |Cite
|
Sign up to set email alerts
|

Issues of spectral quality in clinical 1H‐magnetic resonance spectroscopy and a gallery of artifacts

Abstract: In spite of the facts that magnetic resonance spectroscopy (MRS) is applied as clinical tool in non-specialized institutions and that semi-automatic acquisition and processing tools can be used to produce quantitative information from MRS exams without expert information, issues of spectral quality and quality assessment are neglected in the literature of MR spectroscopy. Even worse, there is no consensus among experts on concepts or detailed criteria of quality assessment for MR spectra. Furthermore, artifact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
367
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(385 citation statements)
references
References 76 publications
6
367
0
7
Order By: Relevance
“…Reported SNR values were calculated in the time domain (free induction decay, FID), by dividing the signal amplitude of the fitted metabolite (GABA or creatine) in the time domain by the standard deviation (SD) of the noise at the end (last 15%) of the acquired FID signal. This is done to obtain a metric for SNR that is independent of line shape 38. SNR was calculated for both coil setups; as spectral resolution of the GABA resonance was similar for both setups, the SNR gain was quantified as the ratio of the two SNR values.…”
Section: Methodsmentioning
confidence: 99%
“…Reported SNR values were calculated in the time domain (free induction decay, FID), by dividing the signal amplitude of the fitted metabolite (GABA or creatine) in the time domain by the standard deviation (SD) of the noise at the end (last 15%) of the acquired FID signal. This is done to obtain a metric for SNR that is independent of line shape 38. SNR was calculated for both coil setups; as spectral resolution of the GABA resonance was similar for both setups, the SNR gain was quantified as the ratio of the two SNR values.…”
Section: Methodsmentioning
confidence: 99%
“…However, often the limited field of view of surface coils does not include these anatomical landmarks, making it necessary to identify bifurcations of vessels and nerves as landmarks. Since the density of methylene protons in pure adipose tissue or bone marrow is about 10 4 times higher than that of IMCL methylene protons in skeletal muscle, the acquisition of spectra needs either efficient suppression of signals from outside the selected voxel (82,108) or suppression of voxels with fat by subsequent post processing in chemical shift imaging (69,109). Slotboom et al (110) suggested a fitting procedure that uses time domain models to fit frequency domain spectra, a method called TDFDFIT.…”
Section: Calibration By the Creatine Signalmentioning
confidence: 99%
“…In obese patients with more prominent EMCL signals, the additional separation of the two resonances of IMCL and EMCL may determine the success or failure of the automatic fitting algorithms (108,110). As a rule of thumb, fitting algorithms need at least a clear dip between the two resonance lines in order to be able to separate them reliably.…”
Section: Influence Of Magnetic Field Strength On 1 H-mr Spectra Of Skmentioning
confidence: 99%
“…In addition to the three books and the paper mentioned above, it is worth reading a recent paper that describes and explains several types of artifacts that may interfere with spectral interpretation (5). A book by de Graaf provides an excellent explanation of the theory, language and technical aspects of in vivo NMR spectroscopy (6).…”
Section: Building a Useful Reference Librarymentioning
confidence: 99%